(untitled) (mathematica didactica, 2021)
Learning is not all about cognitive processes. The best lessons you probably had and remembered were those with moments that caught your emotions and feelings. The main aim of this study is to use potentials of motivational and emotional factors of learning to construct a motivational and emo-tional oriented mathematic lesson. This lesson is the basis for an intervention, which is based on general didactic principles of future-oriented problems. The results suggest that future-oriented education has an impact on interest for mathematics.